Ultrastructure of book gill development in embryos and first instars of the horseshoe crab Limulus polyphemus L. (Chelicerata, Xiphosura) - Farley, Roger D (BioMed Central, 2012)
BACKGROUND: The transmission electron microscope (TEM) is used for the first time to study the development of book gills in the horseshoe crab. Near the end of the nineteenth century the hypothesis was presented for homology and a common ancestry for horseshoe crab book gills and arachnid book lungs. The present developmental study and the author's recent ones of book gills (SEM) and scorpion book lungs (TEM) are intended to clarify early histological work and provide new ultrastructural details for further research and for hypotheses about evolutionary history and relationships. RESULTS: The observations herein are in agreement with earlier reports that the book gill lamellae are formed by proliferation and evagination of epithelial cells posterior to opisthosomal branchial appendages. A cartilage-like endoskeleton is produced in the base of the opisthosomal appendages. The lamellar precursor cells in the appendage base proliferate, migrate outward and secrete the lamellar cuticle from their apical surface. A series of external, posteriorly-directed lamellae is formed, with each lamella having a central channel for hemolymph and pillar-type space holders formed from cells of the opposed walls. This repeated, page-like pattern results also in water channels (without space holders) between the sac-like hemolymph lamellae. CONCLUSIONS: The developmental observations herein and in an earlier study (TEM) of scorpion book lungs show that the lamellae in book gills and book lungs result from some similar activities and features of the precursor epithelial cells: proliferation, migration, alignment and apical/basal polarity with secretion of cuticle from the apical surface and the basal surface in contact with hemolymph. These cellular similarities and the resulting book-like structure suggest a common ancestry, but there are also substantial developmental differences in producing these organs for gas exchange in the different environments, aqueous and terrestrial. For scorpion book lungs, the invaginated precursor cells align in rows and secrete rows of cell fragments that are the basis for the internal, anterior-directed air sacs. The hemolymph sacs of book gills are formed by epithelial evagination or outfolding from the posterior surface of the branchial appendages.